Diverse Effects of Amino Acids on Monascus Pigments Biosynthesis in Monascus purpureus - Yin, Sheng; Zhu, Yiying; Zhang, Bin; Huang, Baozhu; Jia, Ru (Frontiers in Microbiology, 2022)
Amino acids could act as nitrogen sources, amido group donors or bioactive molecules in fungi fermentation and consequently play important roles in Monascus pigments (MPs) biosynthesis. But understanding of effects of various amino acids on MPs biosynthesis is still incomprehensive. In this work, 20 free amino acids were added in fermentation to evaluate their effects on MPs biosynthesis in Monascus purpureus RP2. Six amino acids including HIS, LYS, TYR, PHE, MET, and CYS were selected as the valuable ones as they exerted significant effects on the production yield and even the biosynthesis metabolic curves of MPs. Moreover, the dose-dependent and synergistic effect of valuable amino acids on MPs biosynthesis were observed by tests of serial concentrations and different combinations. And it revealed that HIS and MET were the prominent amino acids with dominant and universal influences on MPs biosynthesis. The analogue compounds of HIS (amitrole) and MET (calcium 2-hydroxy-4-(methylthio)) were added in fermentation and the results further confirmed the extraordinary effects of HIS and MET and their analogues on MPs biosynthesis. Furthermore, gene transcription profile indicated that a differential expression pattern was observed in the PKS cluster responsible for MPs biosynthesis in response to HIS and MET, revealing that they could oppositely regulate MPs biosynthesis in different ways. These findings would benefit understanding of MPs biosynthesis regulation mechanism in M. purpureus and contribute to industrial production of MPs by fermentation.